Representation of Mental Health Disorders in Hollywood Movies - Septiaji, Aji; Kusmana, Suherli (LPPM Institut Pendidikan Nusantara Global, 2025)
Movie as a cultural medium not only reflects social reality but also shapes the construction of meaning towards mental health issues in society. This study focuses on five selected movies, namely A Beautiful Mind (2001), Silver Linings Playbook (2012), Joker (2019), The Perks of Being a Wallflower (2012), and Black Swan (2010). Using Stuart Hall's theory of representation and Freud and Lacan's psychoanalytic approach, this research explores how the main characters are portrayed as experiencing schizophrenia, bipolar disorder, PTSD, depression, and psychosis. The method used is descriptive qualitative analysis. The data were obtained through observation of visual text, dialog, and cinematic symbols. The results show that the movies tend to represent mental health disorders in two main patterns: (1) pathologizing individuals through tragic and dark narratives, and (2) romanticizing mental suffering as part of a character's genius or uniqueness. These representations have an ambivalent impact. On the one hand they raise public awareness about mental health but on the other hand they potentially reinforce negative stereotypes. The result of this research is expected to contribute to cultural, literary, and media psychology studies as well as provide a critical foundation for the production of more ethical and accurate movie that relate on mental health.